AKUNTANSI SYARIAH PADA PERUSAHAAN JASA (IJARAH) - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of the study was to determine the concept of sharia accounting applied to service companies with the Ijarah contract approach. The research method is Descriptive Qualitative with the type of literature. The results showed that a service company is an organization that uses its resources to provide services to its customers. Ijarah is a type of contract that takes benefits (sale of benefits / use value), namely the transfer of the right to use a good and service for a certain time through rental / fee payments without being followed by the transfer of ownership of the goods. The lease referred to by ijarah is an operating lease.PSAK (Statement of Financial Accounting Standards) No. 107 concerning Ijarah, divides the ijarah contract into two, namely: (1) Ijarah without transfer of ownership of the asset, and (2) Ijarah Mutahiyah Bit Tamlik (IMBT)Sharia accounting treatment includes: renters, revenue recognition, depreciation, purchases, costs, purchases, contract completion, transfer of ownership, grants, sales and others.